2020
DOI: 10.7759/cureus.10961
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Various Medical Fields With Emphasis on Radiology: Statistical Evaluation of the Literature

Abstract: Background Artificial intelligence (AI) has significantly impacted numerous medical specialties with high emphasis on radiology. Associated novel diagnostic methods have become a rapidly emerging hot topic, and it is essential to provide insights into quantitative analysis of the growing literature. Purpose The purpose of this study is to highlight future academic trends, identify potential research gaps, and analyze scientific landscape of AI in the field of medicine. The main aim is to explore comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…A high prevalence of AI use was also found among pathologists (71%). These findings are consistent with recently published studies in the literature [21,22] that reflect the suitability of AI tools for pattern recognition and feature classification, which are characteristics that relate most to diagnostic specialties [11]. According to correlation analysis, significant predictors of AI use were primary specialty (V = 0.455; p < 0.001), with radiology having the strongest association (p < 0.001), followed by young age (p < 0.007) and academic qualification.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A high prevalence of AI use was also found among pathologists (71%). These findings are consistent with recently published studies in the literature [21,22] that reflect the suitability of AI tools for pattern recognition and feature classification, which are characteristics that relate most to diagnostic specialties [11]. According to correlation analysis, significant predictors of AI use were primary specialty (V = 0.455; p < 0.001), with radiology having the strongest association (p < 0.001), followed by young age (p < 0.007) and academic qualification.…”
Section: Discussionsupporting
confidence: 94%
“…This could suggest that AI remains a prerogative of the academic community and of younger generations that are more acquainted with digital technology. Among the 14 countries included, Northern European and Western countries had the highest prevalence of AI use, which may indicate a higher tendency for high-income countries to employ AI tools [21,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that in our study radiologists reported a higher inclination to adopt AI tools in their clinical practice compared to other medical specialties. While not present for all indicators assessed, this difference observed for radiologists aligns with the more established use of AI in this medical specialty compared to others [ 90 93 ].…”
Section: Discussionsupporting
confidence: 67%
“…This is evident in the significant number of trials assessing video-based gastroenterology interventions, in contrast to the dominance of image-based radiology algorithms in academic literature and regulatory clearances. [29][30][31][32] This trend appears to be driven by a few groups that account for most video-based gastroenterology trials, indicating that the field of clinical AI trials is still relatively homogeneous in terms of investigators, trial design, and outcome measures. Systems using structured data such as EHRs and waveform data, on the other hand, have employed a mix of decision trees, neural networks, reinforcement learning, and other machine learning techniques.…”
Section: Discussionmentioning
confidence: 99%